Understanding of Islamic Law Enforcement in Some Islamic Countries (Analysis of International Islamic Studies) - Wirawan, Vani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This religious law paper discusses the understanding of Islamic law enforcement in several countries or Islamic empires through analysis and review of hundreds of articles published in high-impact factor journals. Our data collection is carried out with a Google search engine on many scientific data-based publications such as Sagepub, Elsevier, Taylor and France, Academic Paper, and Google Books. Furthermore, the study involved the coding system, evaluation, and in-depth interpretation so that we get an understanding to answer the problems of this study. We design this study as a descriptive qualitative study on secondary data. Based on the results and discussion, we summarize the results; among others, several Islamic countries have made it mandatory for Islamic law to be applied as a whole. However, if it is not an Islamic state, the application is on agreed matters, and Muslims are obliged to fight for it gradually through a constitutional route. These findings should be input for the development of Islamic studies and law in the future.